Prehospital fibrinolysis versus primary percutaneous coronary intervention in ST-elevation myocardial infarction: a systematic review and meta-analysis of randomized controlled trials. Issue 1 (December 2016) - Roule, Vincent; Ardouin, Pierre; Blanchart, Katrien; Lemaitre, Adrien; Wain-Hobson, Julien; Legallois, Damien; Alexandre, Joachim; Sabatier, Rémi; Milliez, Paul; Beygui, Farzin
Abstract Background Primary percutaneous coronary intervention (PPCI) is the preferred reperfusion strategy in patients with ST-elevation myocardial infarction (STEMI), but its benefit over prehospital fibrinolysis (FL) is not clear. Methods We performed a systematic review and meta-analysis of randomized controlled trials in which outcomes of patients with STEMI managed with FL early in the prehospital setting versus PPCI were compared. Results Compared with PPCI, FL was consistently associated with similar rates of short-term (30–90 days) death (relative risk [RR] 0.94, 95 % CI 0.67–1.31) and cardiovascular death (RR 0.95, 95 % CI 0.64–1.4), a decreased risk of cardiogenic shock (RR 0.67, 95 % CI 0.48–0.95), and an increased risk of any stroke (RR 3.57, 95 % CI 1.39–9.17) and hemorrhagic stroke (RR 4.37, 95 % CI 1.25–15.26). FL was also associated with similar rates of 1-year mortality (RR 1.01, 95 % CI 0.75–1.34) and major bleeding (RR 1.31, 95 % CI 0.96–1.78) in comparison with PPCI, but with a notable level (I 2 index 30.5 % and 59.8 %) of heterogeneity among studies. Conclusions Our study suggests that, compared with PPCI, FL performed in the early prehospital setting is associated with similar mortality rates, lower rates of cardiogenic shock, and higher rates of stroke in patients with STEMI. Although the number of studies comparing the two strategies is relatively low, our results support prehospital FL and transfer to hub percutaneous coronary intervention (PCI) centers as a valid alternative to PPCI, allowing potential limitation of resources allocated to developing proximity 24/7 PCI facilities.